2016
DOI: 10.1007/s00213-016-4246-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin depletion eliminates sex differences with respect to context-conditioned immobility in rat

Abstract: The greater display of context-conditioned immobility in males compared with females appears to be serotonin-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
7
1
1
Order By: Relevance
“…Our findings are in agreement with previous reports of similar experiments using Wistar and Lewis rats (Cossio et al, 2016; Maeng et al, 2015; Pryce et al, 1999; Zhao et al, 2018). On the other hand, they contrast with results of other studies using these tests in which males were reported to be more responsive than females (de Jongh et al, 2005; Gresack et al, 2009; Maren et al, 1994; Pettersson et al, 2016). This might reflect the rather different protocols as well as strains of rat used in the latter studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in agreement with previous reports of similar experiments using Wistar and Lewis rats (Cossio et al, 2016; Maeng et al, 2015; Pryce et al, 1999; Zhao et al, 2018). On the other hand, they contrast with results of other studies using these tests in which males were reported to be more responsive than females (de Jongh et al, 2005; Gresack et al, 2009; Maren et al, 1994; Pettersson et al, 2016). This might reflect the rather different protocols as well as strains of rat used in the latter studies.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with recent findings (Day et al 2016), although in contrast to studies on fear discrimination in humans where females show less discrimination than males (Gamwell et al 2015;Lornsdorf et al 2015). Females also displayed lower contextual freezing, consistent with several prior reports in rodents (Pryce et al 1999;Daviu et al 2014;Pettersson et al 2016, although see Keiser et al 2017. When this difference in contextual freezing was subtracted from freezing to each cues, there was a larger difference in freezing to CS+, whereas the main difference in the uncorrected data was primarily in freezing to the CS−.…”
supporting
confidence: 93%
“…Considering other hypotheses for the pathophysiology of depression, especially the monoamine hypothesis, we therefore used the tryptophan hydroxylase inhibitor PCPA to deplete serotonin . The C57BL/6J mice were first injected with PCPA (300 mg/kg) and then injected with TSG (60 mg/kg), and followed by the FST or TST.…”
Section: Resultsmentioning
confidence: 99%